Blue toe syndrome treated with sympathectomy in a patient with acute renal failure caused by cholesterol embolization - Min-Gang Kim; Soo Jin Kim; Jieun Oh; Sung Gyun Kim; Eun Suck Nam; Sang Soo Kang (The Korean Society of Nephrology, 2013)
Blue toe syndrome is the most frequent manifestation of tissue ischemia caused by cholesterol embolization (CE), which can lead to amputation of affected lower extremities, if severe. However, any effective treatment is lacking. We experienced a case of spontaneously presenting blue toe syndrome and concomitant acute renal failure in a patient with multiple atherosclerotic risk factors. CE was confirmed by renal biopsy. Despite medical treatment including prostaglandin therapy and narcotics, the toe lesion progressed to gangrene with worsening ischemic pain. Therefore, we performed lumbar sympathectomy, which provided dramatic pain relief as well as an adequate blood flow to the ischemic lower extremities, resulting in healing of the gangrenous lesion and avoiding toe amputation. This is the first reported case of a patient with intractable ischemic toe syndrome caused by CE that was treated successfully by sympathectomy. Our observations suggest that sympathectomy may be beneficial in some patients with CE-associated blue toe syndrome.